2016
DOI: 10.2108/zs150165
|View full text |Cite
|
Sign up to set email alerts
|

Neo-sex Chromosomes in the Maculipennis Species Group (Dichroplus: Acrididae, Melanoplinae): The Cases of D. maculipennis and D. vittigerum

Abstract: South American melanopline grasshoppers display a disproportionate number of derived karyotypes, including many cases of neo-sex chromosome systems. This is especially true of the genus Dichroplus and its Maculipennis species group. We analyzed the karyotype and neo-sex chromosomes in mitosis and meiosis of Dichroplus maculipennis and D. vittigerum from Argentina using conventional and fluorescent cytogenetic protocols in order to elucidate the behavior and origin of these neo-XY systems in relation to the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In most cases, a centric fusion between the sex chromosome and an autosome is the mechanism responsible that leads to neo‐sex chromosomes. In Acridoidea, the hypothesis widely accepted to explain their formation is also a centric fusion of the X chromosome from the X0♂/XX♀ sex chromosome system with an autosome (Mesa et al ., ; Bidau & Marti, ; Castillo et al ., ,b; Castillo et al ., ; Palacios‐Gimenez et al ., ). The optimization of the character ‘mechanisms that lead neo‐sex chromosome determination system formation’ on the combined ML topology suggests X‐A centric fusion (the classical hypothesis) is the responsible rearrangement involved in neo‐sex chromosome formation, which has persisted in most Ronderosia species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, a centric fusion between the sex chromosome and an autosome is the mechanism responsible that leads to neo‐sex chromosomes. In Acridoidea, the hypothesis widely accepted to explain their formation is also a centric fusion of the X chromosome from the X0♂/XX♀ sex chromosome system with an autosome (Mesa et al ., ; Bidau & Marti, ; Castillo et al ., ,b; Castillo et al ., ; Palacios‐Gimenez et al ., ). The optimization of the character ‘mechanisms that lead neo‐sex chromosome determination system formation’ on the combined ML topology suggests X‐A centric fusion (the classical hypothesis) is the responsible rearrangement involved in neo‐sex chromosome formation, which has persisted in most Ronderosia species.…”
Section: Discussionmentioning
confidence: 99%
“…This centric fusion has resulted in a metacentric neo‐X chromosome, while the homologue of the fused autosome produced a telocentric neo‐Y (White, ,b, ). The cytogenetic analysis of several species of Dichroplini revealed that similar characteristics to those observed in autosomes, not involved in rearrangement, persist in the XR arm of the neo‐X (Mesa et al ., ; Castillo et al ., ,b, ).…”
Section: Introductionmentioning
confidence: 99%
“…elongatus group analyzed here shared several taxonomic characters [ 4 , 39 ], and at the chromosomal level show slight variations due to the occurrence of chromosome rearrangements compared with the D . maculipennis species group [ 6 , 40 ]. Despite the standard male chromosome number (2n = 23) observed in the species analyzed here, we noticed a diversification pattern concerning the multigene family genes, probably caused by micro chromosomal rearrangements that led to the divergence of the chromosomal markers employed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of chromosome variation in number (2n) and chromosome morphology (FN = the number of chromosome arms including the X chromosome) are recorded for the D . maculipennis species group [ 6 ]. In fact, comprehensive cytogenetic studies in this species group regarding population cytogenetics ( D .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation